405 Myopericarditis after SARS-CoV-2 MRNA vaccination: casual or causal relationship?. (8th December 2021) - Golino, Michele; Licciardello, Claudio; Matteo, Federica; Giovenzana, Fulvio Lorenzo Francesco; Franzosi, Cinzia; Blasi, Federico; Genoni, Paola; Seganfreddo, Fancesca; Cadonati, Cristina; Morello, Matteo; Di Martino, Sara Elena; Marazzato, Jacopo; et al.
Abstract: Aims: Myopericarditis have been reported as rare event after SARS-CoV-2 vaccination with mRNA-1273 and BNT162b2. However, these data referred to the month of May 2021, when only a few people under the age of 30 had been vaccinated. The aim was to report cases diagnosed with myopericarditis short after vaccination admitted to our hospital. Methods and results: An observational study was performed recording all cases of patients (pts) hospitalized for myopericarditis which occurred within 14 days of SARS-CoV-2 mRNA vaccination. From June to August 2021, 12 pts were hospitalized for myopericarditis; four of them (33%) were young male pts (29 ± 12 years old) with no history of CVDs or SARS-CoV-2 infection but with a recent second dose of Covid-19 mRNA-1273 vaccine (mean interval from the injection 3 ± 2 days). ECG showed diffuse ST-segment elevation without specularity (Figure 1). SARS-CoV-2 molecular swab tested negative; laboratory (lab) test showed a slight increase of white blood cells (11 267 ± 1047 10 8 /l) and a marked increase of C-reactive protein (78 ± 79 mg/l), troponin T (179 ± 179 ng/l), and Nt-proBNP (876 ± 198 ng/l); transthoracic echocardiogram showed normal left ventricle ejection fraction (mean 55 ± 3%) and in one case only mild pericardial effusion; chest X-ray showed pleural effusion in one case only. Pts were then hospitalized for an average of 7 ± 2 days and an anti-inflammatory therapy based on acetylsalicylic acid and colchicine (in one case also with cortisone) was established. In the following days, pts gradually recovered and were discharged home. After 10 days, two pts underwent a cardiac magnetic resonance imaging (cMRI) revealing myocardial oedema and late gadolinium enhancement in the subepicardial and midmyocardium, along the basal and mid-apical lateral wall; due to relative contraindications, the same examination was scheduled later for the other two pts. These cases deserve specific considerations on the causal relationship between heart inflammation and SARS-CoV-2 mRNA vaccines. Among the various pathophysiological hypothesis there is the high levels of antibodies that mRNA vaccines can generate in young male subjects or the consideration of mRNA as a natural adjuvant capable of activating disproportionately the innate immune system; in both cases, the result is an immune overreaction that can affect various organs including the heart. Conclusions: Although the number of our cases is small and all pts recovered in a short time, the timing of symptoms and the similarities in clinical findings and lab characteristics call for further investigations.